SKRINING FITOKIMIA DAN FORMULASI SEDIAAN MASKER PEEL-OFF EKSTRAK ETANOL GAMBIR (Uncaria gambir (W. HUNTER) ROXB) SECARA PERKOLASI - Hasanah, Fenny (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2019)
Gambir (Uncaria gambir (W. Hunter) Roxb) contains catechins, quercetin, alkaloids, flavonoids and tannins that have a role as antioxidants. The objectives of this research is to observe whether or not extract etanol Gambir can be formulated by Peel Off mask preparation form. In this experimental methods, the extract was obtained by percolate extraction using 80% ethanol, and then concentrated with a rotary evaporator at 40ºC and dried by evaporation over a water bath at a temperature around 60ºC. Phytochemical screening was used to test the content of the chemical compounds found in gambir and gambir ethanol extract. The results of the screening test showed the presence of alkaloids, flavonoids, saponins, and tannins. This research concluded that extract of ethanol of gambir can be formulated in the form of peel-off mask in a homogeneous preparation that has no skin irritation, pH 5.2 to 5.6 and stable in storage for 4 weeks.